The Legitimacy of Regional Integration in Europe and the Americas
XIV, 312 p.
Keywords: Based on cutting-edge research, this edited volume examines how citizens and political elites perceive the legitimacy of regional integration in Europe and the Americas. It analyses public opinion and political discourse on the EU, NAFTA and MERCOSUR, arguing that legitimation patterns shape the development of regional governance.